2003
DOI: 10.1091/mbc.e02-07-0390
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenylcysteine Carboxyl Methyltransferase Activity Modulates Endothelial Cell Apoptosis

Abstract: Extracellular ATP, adenosine (Ado), and adenosine plus homocysteine (Ado/HC) cause apoptosis of cultured pulmonary artery endothelial cells through the enhanced formation of intracellular S-adenosylhomocysteine and disruption of focal adhesion complexes. Because an increased intracellular ratio of S-adenosylhomocysteine/S-adenosylmethionine favors inhibition of methylation, we hypothesized that Ado/HC might act by inhibition of isoprenylcysteine-O-carboxyl methyltransferase (ICMT). We found that N-acetyl-S-ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 47 publications
5
51
0
1
Order By: Relevance
“…Since the homeostatic levels of SAH are critically important on account of SAH being a potent productinhibitor of many SAM-dependent methyltransferases [58], we postulate a critical role of one or more liver methyltransferases in preventing hepatocyte apoptosis. Recent studies have shown that the carboxyl methylation reaction of small GTPases is a crucial activation step that facilitates these proteins to participate in anti-apoptotic signaling pathways [59]. We speculate that inhibition of the critical methyltransferase (such as isoprenyl cysteine methyltransferase) by elevated intracellular SAH levels may be responsible for adenosine-induced apoptosis in hepatocytes.…”
Section: Discussionmentioning
confidence: 84%
“…Since the homeostatic levels of SAH are critically important on account of SAH being a potent productinhibitor of many SAM-dependent methyltransferases [58], we postulate a critical role of one or more liver methyltransferases in preventing hepatocyte apoptosis. Recent studies have shown that the carboxyl methylation reaction of small GTPases is a crucial activation step that facilitates these proteins to participate in anti-apoptotic signaling pathways [59]. We speculate that inhibition of the critical methyltransferase (such as isoprenyl cysteine methyltransferase) by elevated intracellular SAH levels may be responsible for adenosine-induced apoptosis in hepatocytes.…”
Section: Discussionmentioning
confidence: 84%
“…These modifi cations allow CAAX proteins to associate with cellular membranes and promote protein-protein interactions ( 34 ). The methylation reactions require SAM as a methyl group donor to produce methylated Ras, thus linking methionine metabolism to modulation of MEK/ERK1/2 activation.…”
Section: Inhibition Of Methyltransferase Suppressed Mek/ Erk1/2 Activmentioning
confidence: 99%
“…The methylation reactions require SAM as a methyl group donor to produce methylated Ras, thus linking methionine metabolism to modulation of MEK/ERK1/2 activation. Indeed, intracellular SAH level is negatively related to ICMT activity ( 34 ). In addition, 3-Deazaadenosine, a potent inhibitor of S-adenosylhomocysteine hydrolase, whose inhibition induces intracellular SAH accumulation, prevents vascular smooth muscle cell proliferation and neointima formation by interfering with Ras methylation and thereby with mitogenic activation of ERK1/2 ( 36 ).…”
Section: Inhibition Of Methyltransferase Suppressed Mek/ Erk1/2 Activmentioning
confidence: 99%
“…Subsequent pharmacologic studies have also provided evidence that inhibition of Icmt-catalyzed methylation presents a potential approach to controlling cell prolifera-tion (Kramer et al, 2003;Anderson et al, 2005;WinterVann et al, 2005;Blum et al, 2008). To date, the most potent pharmacologic agent targeting Icmt is a compound termed as cysmethynil, originally identified in a screen of a small molecule library containing diverse scaffolds (Baron et al, 2007).…”
Section: Introductionmentioning
confidence: 99%